BIOSYNTHESIS OF NITRO COMPOUNDS I. : Nitrogen and Carbon Requirements for the Biosynthesis of β-Nitropropionic Acid by Penicillium atrovenetum - Shaw, Paul D. (1964)
Shaw, Paul D. (University of Illinois, Urbana), and Nancy Wang. Biosynthesis of nitro compounds. I. Nitrogen and carbon requirements for the biosynthesis of β-nitropropionic acid by Penicillium atrovenetum. J. Bacteriol. 88:1629–1635. 1964.—β-Nitropropionic acid was produced by Penicillium atrovenetum when this fungus was grown on a Raulin-Thom medium in shake flasks. The nitro compound was formed in the early stages of growth, and the total amount in the medium decreased when the fungus reached the end of the log phase. When increasing amounts of nitrate were substituted for the ammonia in the growth medium, production of β-nitropropionic acid decreased. Aspartic acid did not promote the synthesis of the nitro compound unless either ammonium chloride or sodium tartrate was also added to the medium. The addition of small amounts of hydroxylamine or sodium nitrite to the Raulin-Thom medium stimulated β-nitropropionic acid production to a greater degree on a molar basis than the amount of hydroxylamine or nitrite added. The nature of possible precursors to the nitro group of β-nitropropionic acid is discussed.